Genomic Insights into Blood Pressure Regulation: Exploring Ion Channel and Transporter Gene Variations in Jordanian Hypertensive Individuals - Mansour Abdullah Alghamdi; Laith AL-Eitan; Rasheed Ibdah; Islam Bani Khalid; Salma Darabseh; Maryam Alasmar; Asaad Ataa (Medicina)
Background and Objectives: Hypertension (HTN) constitutes a significant global health burden, yet the specific genetic variant responsible for blood pressure regulation remains elusive. This study investigates the genetic basis of hypertension in the Jordanian population, focusing on gene variants related to ion channels and transporters, including KCNJ1, WNK1, NPPA, STK39, LUC7L2, NEDD4L, NPHS1, BDKRB2, and CACNA1C. Materials and Methods: This research involved 200 hypertensive patients and 224 healthy controls. Whole blood samples were collected from each participant, and genomic DNA was extracted. The genetic distribution of the polymorphisms was analyzed. The haplotype frequencies were investigated using the SNPStats web tool, and the genotype and allele frequencies of the studied variants were assessed using the χ2 test. Results: Sixteen single nucleotide polymorphisms (SNPs) from nine genes were evaluated. A significant association was observed between the rs880054 variant of the WNK1 gene and hypertension susceptibility, with the T allele elevating the risk of hypertension. This association remained important in the codominant model (p = 0.049) and the dominant model (p = 0.029). In addition, rs880054 was associated with clinical characteristics such as triglyceride levels and cerebrovascular accidents (p-value > 0.05). Conclusions: Our findings reveal a significant link between the rs880054 SNP and an increased hypertension risk, suggesting that variations in WNK1 may be crucial in regulating blood pressure. This study provides new insights into the genetic factors contributing to hypertension and highlights the potential of WNK1 as a target for future therapeutic interventions.